Hazard Identification, Risk Assessment and Control (HIRAC) on Water Solid Contents Determination at Environmental Chemistry Laboratory of President University - Manik, Yosef Barita Sar; Mayriza, Azka Leona; Putri, Brilian Maulani; Keisha Fawwaaz; Huri, Khalila Kireina; Maulidinnisa, Vira Puspita (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
This study conducted a Hazard Identification and Risk Assessment (HIRA) on Solid Contents Experiment that is taking place in the President University Environmental Engineering Laboratory. The main objective in this study is to identify potential hazard during experiment, to understand the risk level of hazards in the Environmental Engineering Laboratory, and to propose strategies and give improvement in laboratory practices. The methods used in this study is Hazard Identification, Risk Assessment and Control (HIRAC). As the result, the hazards that are identified in this study is slip and fall, respiratory hazard, fragile object, burn and physical injury, and electrical hazard. There are 18 hazards observed, and priority sorting is done to identify which hazard is high and medium in level and needs further caution, which turned out to be 12 medium to high hazards. The most critical hazard is pouring the water sample inti the vacuum using volumetric glass, because it has risk of slipping, falling, and handling when the water sample is spilled, and it is also a fragile object. So, this study identifies the effectiveness of HIRA method, finding steps that should be done to improve the operationsl conditions of the laboratory, and update practical education afterwards.